Ideological Dynamics of PKS and Gelora in Indonesian Democracy - Munandar, Aris; Suwendi, Suwendi (Jurnal Review Politik, 2025)
This study analyzes the ideological construction of the Prosperous Justice Party (PKS) and the Indonesian People’s Wave Party (Gelora), focusing on differences in principles, ideological orientation, communication strategies, and socio-political base segmentation following the internal fragmentation that led to Gelora’s emergence as a splinter of PKS. The study addresses a research gap concerning how new parties build ideological legitimacy in the post-reform political era. A descriptive qualitative approach was employed through a literature study, drawing data from official party documents, scholarly articles, and online media coverage. The analysis applies Paul Lucardie’s new party theory, which categorizes parties as prophets, purifiers, or challengers. The findings reveal that PKS maintains its character as a conservative Islamic party, while Gelora emerges as an ideological challenger promoting moderate Islam, inclusive nationalism, and a geopolitical agenda. Both parties’ ideologies are shaped through official documents, public narratives, communication styles, and symbolic strategies in response to democratic and pluralistic dynamics in Indonesia.